1998
DOI: 10.1074/jbc.273.4.2161
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Muscle Cell Hypertrophy and Apoptosis Induced by Distinct Members of the p38 Mitogen-activated Protein Kinase Family

Abstract: p38 mitogen-activated protein (MAP) kinase activities were significantly increased in mouse hearts after chronic transverse aortic constriction, coincident with the onset of ventricular hypertrophy. Infection of cardiomyocytes with adenoviral vectors expressing upstream activators for the p38 kinases, activated mutants of MAP kinase kinase 3b(E) (MKK3bE) and MAP kinase kinase 6b(E) (MKK6bE), elicited characteristic hypertrophic responses, including an increase in cell size, enhanced sarcomeric organization, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
629
3
8

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 791 publications
(672 citation statements)
references
References 51 publications
32
629
3
8
Order By: Relevance
“…In cardiac myocytes, expression of activated forms of MKK3 and MKK6 led to different responses; active MKK3 caused apoptosis while active MKK6 invoked hypertrophy. 36 Studies with MKK3 À/À and MKK6 À/À mice also revealed distinct functions of these MKKs in immune responses. 37 The lack of inhibitory effect of MKK3-DN on Oc differentiation in spite of the decrease in NFATc1 induction by RANKL (Figures 5d and 6b) is puzzling in view of the reports that suggested NFATc1 as a key regulator of osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In cardiac myocytes, expression of activated forms of MKK3 and MKK6 led to different responses; active MKK3 caused apoptosis while active MKK6 invoked hypertrophy. 36 Studies with MKK3 À/À and MKK6 À/À mice also revealed distinct functions of these MKKs in immune responses. 37 The lack of inhibitory effect of MKK3-DN on Oc differentiation in spite of the decrease in NFATc1 induction by RANKL (Figures 5d and 6b) is puzzling in view of the reports that suggested NFATc1 as a key regulator of osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant adenoviruses (Ad) expressing activated MKK3bE, MKK6bE, green fluorescent protein (GFP) and dominant negative p38 MAP kinase α driven by a cytomegalovirus promoter (Ad/MKK3bE, Ad/MKK6bE Ad/CMV-GFP and Ad/ p38αdn), respectively have been described previously. 29,30 Cell Viability Assay. Cells were seeded in the same medium on 96-well plates at densities of 1 x 10 4 /well and held at 37˚C for 1 day before treatment with TRAIL protein (R & D Systems, Inc. Minneapolis, MN), anisomycin (Calbiochem, San Diego, CA), or adenovectors.…”
Section: Methodsmentioning
confidence: 99%
“…the p38 MAPK, play a pivotal role in the development of heart failure, including diabetic cardiomyopathy [10]. Via its signalling cascade, the p38 MAPK modulates genes that regulate myocyte apoptosis, cellular hypertrophy, cardiac fibrosis, and cardiac cytokine-mediated inflammation [11][12][13]. Because the p38 MAPK is not only upregulated and phosphorylated by ischaemia [14], but also, for example, by angiotensin II [15], oxidative stress [16], and high glucose levels [10], inhibition of p38 MAPK could be a potent new therapeutic option for treatment of diabetic cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%